TQM implementation in service industries - a case study of an educational institution. - Foo, Pearline Li Ping. (2008)
In the course of our study, we have tried to trace the emerging trends of TQM in service industries. We have also formulated a conceptual framework that we hope will serve as a guide in the pursuit of TQM within education institutions. For the purpose of our study, we have also commented on the implementation model of Temasek Polytechnic with reference to our proposed conceptual model, which has included the core elements of TQM–customer focus, continuous improvement and total participation.